Typology The Study Of Hadith Orientalist: Thinking A. Kevin Reinhart In “Juynbolliana, Gradualism, The Big Bang, And Hadith Study In The Twenty First Century” - Hasibuan, Ummi Kalsum (UIN Sayyid Ali Rahmatullah Tulungagung, 2020)
Abstract This article explores the typology of orientalist hadith studies with a focus on one of the works of orientalist figures, namely: A. Kevin Reinhart with the title